2022
DOI: 10.1007/s00404-022-06758-z
|View full text |Cite
|
Sign up to set email alerts
|

Predicting success of intrauterine insemination using a clinically based scoring system

Abstract: Purpose To develop a predictive score for the success of intrauterine insemination (IUI) based on clinical parameters. Methods We performed a retrospective cohort study evaluating the homologous IUI cycles performed at a single university-based reproductive medical center between 2009 and 2017. The primary outcome measure was pregnancy, defined as positive serum human chorionic gonadotropin (hCG) 12–14 days after IUI. Predictive factors for pregnancy after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Our study advocated for a maximum of four consecutive IUI cycles to optimize the probability of pregnancy, a suggestion consistent with certain literature advocating for cycle limits (Zippl et al, 2022).…”
Section: Cumulative Pregnancy Ratessupporting
confidence: 84%
“…Our study advocated for a maximum of four consecutive IUI cycles to optimize the probability of pregnancy, a suggestion consistent with certain literature advocating for cycle limits (Zippl et al, 2022).…”
Section: Cumulative Pregnancy Ratessupporting
confidence: 84%
“…Spermiogram parameters play a crucial role in assessing couples' suitability for an IUI cycle, continuously attracting research attention and clinical interest. However, previous reports indicated that no universally accepted parameter from pre-wash or post-wash semen analyses reliably predicts the outcome of IUI treatment [22][23][24][25]. In our study, patients with a post-wash TPMSC of <1 × 10 6 were not included.…”
Section: Discussionmentioning
confidence: 97%
“…Patient drop-off or unwillingness to return after initial cycle failure represents a significant limitation in modern IVF, and the major physical, emotional, and financial burdens women undergo for treatment are important contributors to this drop-off. While less invasive options such as intrauterine insemination (IUI) may be successful for some, the success rates are extraordinarily low, with some studies showing a clinical pregnancy rate of 10% or less per cycle and pose inherent challenges in same-sex couples who wish to utilize reciprocal IVF treatment (43). This study shows that minimal COS plus OSC-IVM is highly tolerated and potentially similarly efficacious compared to conventional COS, with higher satisfaction and willingness to repeat.…”
Section: Discussionmentioning
confidence: 99%